ANALISIS OVERALL EQUIPMENT DAN SIX BIG LOSSES PADA MESIN RUI PACKING DI PT NU - Alloysius Vendhi Prasmoro; Arif Nuryono; Jasan Supratman; Abdurahman Rizki Arfiansyah (CV. Denasya Smart Publisher, 2025)
The background of this research is the problem that occurs, namely the large number of downtime on the rui machine at PT. NU. The company has a standard tolerance on downtime which is around 2.5%, while the amount of downtime that occurs in the production process exceeds the specified tolerance limit. Therefore, it is necessary to conduct research that aims to determine the dominant problem causing downtime that occurs on the machine and determine the proposed improvements to reduce the number of downtime by using the Overall Equipment Effectiveness and Six Big Losses method. The results of the study indicate that the OEE value on the rui machine for one year is 69%, this value is still below the world standard. The dominant causes of downtime on the machine are Equipment Failure Losses of 42% and Defect Losses of 30.6% of all time losses. Furthermore, the proposed improvements are to repair spare parts on time, provide spare part stock for quick repair, and provide training to employees about the importance of care and maintenance on the machine.